Assessment of male CVID patients for mutations in the Btk gene: how many have been misdiagnosed? - Weston, SA; Prasad, M; Mullighan, C; Chapel, H; Benson, E (2001)
The presentation of hypogammaglobulinaemia in young males without a family history of immunodeficiency can pose a diagnostic problem. In the past, the presence of B-cells has suggested a diagnosis of common variable immunodeficiency (CVID), although genotypic analysis has now clarified that individuals with B cells may have mutations in their Btk gene. In order to address the issue of how many male individuals with a clinical diagnosis of CVID do in fact have mutations in the Btk gene, we analysed a group of 24 male patients. Single-strand conformation polymorphism (SSCP) analysis was used to screen the patient cohort for mutations in the Btk gene. Given the size of the Btk gene, the number of patients in the cohort and the amount of available DNA, multiplex PCR reactions were utilized to span the 19 exons and promoter region of the gene. Where abnormal migration patterns were observed with multiplex PCR reactions, in nine of the 24 patients, the individual Btk gene fragments were re-amplified and analysed again by SSCP. Following this analysis, four patients continued to demonstrate abnormal SSCP migration patterns. However, direct sequencing of the relevant Btk gene fragments for these four CVID patients revealed a mutation in only one patient. The mutation was the previously described polymorphism at position 2031 of Btk gene within exon 18. These results indicate that caution should be taken with the application of SSCP analysis to mutation detection. While it has a role to play in screening large patient cohorts, direct sequencing is a necessary adjunct to such analysis. Finally, the clinical diagnosis of CVID in this cohort successfully excluded males with Btk mutations.